Evidence for Chilling-Induced Oxidative Stress in Maize Seedlings and a Regulatory Role for Hydrogen Peroxide. - Prasad, T. K. (1994)
We have taken advantage of an acclimation phenomenon in a chilling-sensitive maize inbred to investigate the molecular, biochemical, and physiological responses to chilling in preemergent maize seedlings. Three-day-old seedlings were exposed to 4[deg]C for 7 days and did not survive chilling stress unless they were preexposed to 14[deg]C for 3 days. cDNAs representing three chilling acclimation-responsive (CAR) genes were isolated by subtraction hybridization and differential screening and found to be differentially expressed during acclimation. Identification of one of these CAR genes as cat3, which encodes the mitochondrial catalase3 isozyme, led us to hypothesize that chilling imposes oxidative stress in the seedlings. Hydrogen peroxide levels were elevated during both acclimation and chilling of nonacclimated seedlings. Further molecular and biochemical analyses indicated that whereas superoxide dismutase activity was not affected, the levels of cat3 transcripts and the activities of catalase3 and guaiacol peroxidase were elevated in mesocotyls during acclimation. Accumulation of H2O2 following a short treatment with aminotriazole, a catalase inhibitor, indicated that catalase3 seems to be an important H2O2-scavenging enzyme in the seedlings. Control 3-day-old seedlings pretreated with H2O2 or menadione, a superoxide-generating compound, at 27[deg]C induced chilling tolerance. Both of these chemical treatments also increased cat3 transcripts and catalase3 and guaiacol peroxidase activities. We suggest that peroxide has dual effects at low temperatures. During acclimation, its early accumulation signals the production of antioxidant enzymes such as catalase3 and guaiacol peroxidase. At 4[deg]C, in nonacclimated seedlings, it accumulates to damaging levels in the tissues due to low levels of these, and perhaps other, antioxidant enzymes.